Brutes and Inequalities in African Society: Appraisal of Femi Osofisan's once upon Four Robbers and Athol Furgard's Sizwe Bansi is Dead - Okocha Godfrey Obiajulu; Tunde Obado Oliogu (International Review of Social and Cultural Studies, 2025)
Brutality and inequality in African society are common afflictions that have ravaged the continent irrespective of moral and religious inclinations. This study explores how Africans are maltreated and deprived of their rights and privileges by their leaders and political elites. The research focuses on two African plays from distinct regions where these issues resonate: Femi Osofisan's Once Upon Four Robbers (1980) and Athol Fugard's Sizwe Bansi Is Dead (1972). Both plays share common themes and adopt comparable dramatic techniques. Osofisan's work examines the injustice and brutality that the Nigerian government inflicts on many households. Robbers in the play are publicly executed without regard to human dignity, and Osofisan questions both the rationale behind these executions and the root causes of theft. Fugard was disturbed by the inhumane treatment of Black South Africans during the apartheid regime. He explores themes of oppression, death, poverty, racism, hypocrisy, and other social vices to underscore the inhumanity. Sizwe Bansi Is Dead mirrors the monstrosities of apartheid, portraying the bitterness experienced by Black Africans characterized by repressive labor policies, insecurity, slavery, and other reprehensible laws. Fugard's dramatic techniques are outstanding; he employs symbolism, irony, monologue, and collaborative efforts to communicate his message effectively. This paper aims to enhance the evaluation of these dramatic works and provide insights into issues of collaboration, revolution, treachery, injustice, and determination. The theoretical framework adopted for this study is postcolonial theory, which is relevant to the evaluation of literary representations in Nigeria and South Africa respectively.